Physical Therapy Outcome Measures for Assessment of Lower Extremity Chronic Pain-Related Function in Pediatrics. Issue 2 (April 2019) - Mirek, Elizabeth; Logan, Deirdre; Boullard, Kimberly; Hall, Amber M.; Staffa, Steven J.; Sethna, Navil
Abstract : Purpose: To assess the clinical utility of 5 physical therapy (PT) outcome measures in quantifying functional changes in pediatric lower extremity chronic pain treated at a hospital-based interdisciplinary rehabilitation center. Design: This was a cross-sectional study with retrospective review of 173 individuals, 8 to 18 years old, treated from June 2008 to 2013. Methods: The measures used were the Timed Up and Go, Timed Up and Down Stairs, Bruininks-Oseretsky Test of Motor Proficiency, Second Edition, 6-minute walk test, and Lower Extremity Functional Scale. Participant performance was correlated with demographic characteristics, the Functional Disability Index, Multidimensional Anxiety Scale for Children, Child Depression Inventory, and Canadian Occupational Performance Measure. Results: Scores from all 5 PT measures showed significant improvement following treatment. Functional Disability Index correlated to every PT measure except the 6-minute walk test. Conclusions: This study supports the clinical use of these PT measures to track functional progress after rehabilitative treatment of lower extremity chronic pain-related disability. Abstract : Assesses the clinical utility of 5 PT outcome measures in quantifying functional changes in pediatric lower extremity chronic pain treated at a hospital-based interdisciplinary rehabilitation center.